Cerebrospinal Fluid Biomarkers for the Diagnosis of Alzheimer Disease in South Korea. (January 2017) - Park, Sun Ah; Chae, Won Seok; Kim, Hyeong Jun; Shin, Ho Sik; Kim, Saeromi; Im, Ji Young; Ahn, Sang Il; Min, Kyoung Dae; Yim, Soo Jae; Ye, Byoung Seok; Seo, Sang Won; Jeong, Jee Hyang; et al.
Abstract : Laboratory-specific reference values for cerebrospinal fluid (CSF) Alzheimer disease (AD) biomarkers are necessary. Our objective was to apply well-known CSF biomarkers and redetermine their diagnostic cutoff values for AD in South Korea. CSF samples from matched control subjects (n=71), patients with AD dementia (ADD, n=76), and other neurological disorders with cognitive decline (OND, n=47) were obtained from 6 Korean dementia clinics according to a standardized protocol. CSF biomarker concentrations were measured using enzyme-linked immunosorbent assay. CSF biomarkers differed significantly between the ADD and control groups ( P <0.001 for all), and between the ADD and OND groups ( P <0.001 for all). The areas under the curve in differentiation of ADD from control subjects were 0.97 for Aβ42, 0.93 for total tau (tTau), 0.86 for pTau, and 0.99 for both tTau/Aβ42 and pTau/Aβ42 ratios. Our revised cutoff value for Aβ42 was higher than our previous one, whereas the values for the Tau proteins were similar. The tTau/Aβ42 ratio had the highest accuracy, 97%. Our findings highlight the usefulness of CSF AD biomarkers in South Korea, and the necessity of continually testing the reliability of cutoff values.